Four new troglophilous species of the genus Belisana Thorell, 1898 (Araneae, Pholcidae) from Guizhou Province, China - Chen, Hui-Ming; Zhang, Feng; Zhu, Ming-Sheng (Zootaxa, 2009)
Four new troglophilous, six-eyed pholcid spiders belonging to the genus Belisana from caves in Shuicheng County, Zhijing County, Xishui County and Yanhe Tujia Autonomic County, Guizhou, China, are diagnosed, described and illustrated: Belisana douqing sp. nov., B. daji sp. nov., B. xishui sp. nov., and B. yanhe sp. nov..